Melatonin Inhibits Migration and Invasion in LPS-Stimulated and -Unstimulated Prostate Cancer Cells Through Blocking Multiple EMT-Relative Pathways [Retraction] - Tian QX; Zhang ZH; Ye QL; Xu S; Hong Q; Xing WY; Chen L; Yu DX; Xu DX; Xie DD (Dove Medical Press, 2024)
Tian QX, Zhang ZH, Ye QL, et al. J Inflamm Res. 2021;14:2253–2265. We, the Editors and Publisher of Journal of Inflammation Research, have retracted the following article. Following publication of the article, the authors raised concerns regarding the duplication of images from Figure 1. Specifically, The images for Figure 1A, PC-3, MT, 12h and 24h have been duplicated. The images for Figure 1B, DU145, MT and Figure 1C, PC-3, Control and MT+LPS have been duplicated. The images for Figure 1C, DU145, MT+LPS and PC-3, MT have been duplicated. The authors explained the incorrect use of images occurred during figure preparation and did provide some of the original data for the study. However, the provided data and the authors explanation regarding the duplicated images did not sufficiently alleviate the journal’s concerns regarding the validity of the findings. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article and the authors do not agree with this decision. We have been informed in our decision-making by our editorial policies and COPE guidelines. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.